Method for controlling multiple-injection of gaseous fuel in a direct injection engine. - Sahari, Barkawi (2005)

(untitled)
The present invention provides a method for controlling multiple direct injection in a combustion chamber within one engine cycle in vehicles by using different fuel injection algorithms according to the specific engine state, wherein the homogeneous mode (H-mode) is used to obtain better engine performance while the stratification mode (S-mode) is used when better fuel consumption is required.